PENGARUH PENERAPAN SISTEM INFORMASI KEUANGAN DAERAH, PENGENDALIAN INTERN, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA KEUANGAN SKPD KABUPATEN SIGI - Marjoni, Marjoni (Katalogis, 2018)
The study is aimed to determine and analyze significant influence of the application of regional financial information system, internal control, and human resource competency simultaneously on financial performance of governmental working units in Sigi District; significant influence of the application of regional financial information system, partially on financial performance of governmental working units in Sigi District; significant influence of internal control, partially on financial performance of governmental working units in Sigi District; significant influence of human resource competency, partially on financial performance of governmental working units in Sigi District. The results of the study highlight that the application of regional financial information system, internal control, and human resource competency simultaneously have significant influence on financial performance of governmental working units in Sigi District; the application of regional financial information system significantly influence financial performance of governmental working units in Sigi District; internal control significantly influence financial performance of governmental working units in Sigi District; human resource competency significantly influence financial performance of governmental working units in Sigi District. Â Â